CD244 represents a new therapeutic target in head and neck squamous cell carcinoma. Issue 1 (26th March 2020) - Agresta, Laura; Lehn, Maria; Lampe, Kristin; Cantrell, Rachel; Hennies, Cassandra; Szabo, Sara; Wise-Draper, Trisha; Conforti, Laura; Hoebe, Kasper; Janssen, Edith M
Abstract : Background: Developing novel strategies to overcome the immunosuppressive tumor microenvironment is a critically important area of cancer therapy research. Here, we assess the therapeutic potential of CD244 (2B4/signaling lymphocyte activation molecule family 4), an immunoregulatory receptor found on a variety of immune cells, including exhausted CD8 + T cells, dendritic cells (DCs), and myeloid-derived suppressor cells (MDSCs). Methods: Using de-identified human tumor and blood samples from patients with head and neck squamous cell carcinoma (HNSCC) and HNSCC models in WT and CD244 -/- mice, we assessed the therapeutic potential of CD244 using flow cytometry, RT-PCR, Luminex immunoassays and histopathological analyses. Results: Compared with healthy tissues, tumor infiltrating CD8 + T cells from HNSCC patients and a HNSCC mouse model showed significant increased expression of CD244 expression that correlated with PD1 expression. Moreover, CD244 was increased on intratumoral DC and MDSC and high CD244 expression correlated with PD-L1 expression and increased spontaneous expression of immune-suppressive mediators. In addition, CD244 activation inhibited production of proinflammatory cytokines in human DC in vitro. Importantly, CD244 -/- mice showed significantly impaired tumor growth of HNSCC and interventional treatment of WT mice with anti-CD244 monoclonal antibody significantly impaired the growth of established HNSCC tumors and increased tumor-infiltrating CD8 + T cells. Conclusions: Together these data suggest that CD244 contributes to the overall immune-suppressive environment and therefore has potential as a new immunotherapy target in the treatment of malignancies.